Analisis Kendala dan Solusi dalam Penerapan Kurikulum Merdeka pada Jurusan Teknik Listrik dan Mesin di SMK PGRI 1 Kota Serang - Enjel Rosiana; Vanitour Ayu Pramukti; A. Dhyta Maulana; Arjuna Fikri Tri Firmansyah; Sukira Sukira; Rifky Rajaba Philipo; Walid Ilhamul Nayat Nasution; Al Fikri Muhammad Ramdani; Suhendar Suhendar; Hendra Firmansyah (Universitas Palangka Raya, 2024)
The implementation of the Merdeka Curriculum in Vocational High Schools (SMK) aims to enhance the quality of vocational education by promoting flexible learning that aligns with industry needs and fosters 21st-century skills. In the Electrical and Mechanical Engineering departments, this curriculum emphasizes project-based learning to develop both technical and soft skills. However, the application of the Merdeka Curriculum at SMK PGRI 1 Kota Serang faces several challenges that need to be addressed for its effective implementation. One of the key challenges is the adaptation of students to new learning methods, particularly those involving independent learning and critical thinking. Additionally, limited time for implementing projects and integrating them into the curriculum often hampers optimal learning outcomes. Teachers also face difficulties in aligning project-based learning with existing curriculum structures, affecting the continuity of lessons. To overcome these challenges, several strategies need to be adopted, such as redesigning flexible schedules to allow more time for project-based activities, developing practical and relevant project modules, and fostering collaboration among educators to improve teaching practices. By addressing these issues, the Merdeka Curriculum can be effectively implemented, ensuring that students in the Electrical and Mechanical Engineering departments acquire industry-relevant skills. This study aims to provide insights and recommendations for optimizing curriculum implementation